A prospective randomized study to compare hemodynamic changes and post-operative outcome of intravenous buprenorphine versus epidural buprenorphine in patients undergoing abdominal surgeries under general anesthesia - Youvaraj M; Jitendra Agrawal; Brajesh Kumar; Sourabh Shrivastava; Preeti Goyal (Asian Journal of Medical Sciences, 2023)
Background: Post-operative pain following major abdominal surgeries is accompanied with multitude of negative consequences, including increased morbidity, impaired physical function, and slow recovery. Opioids are the gold standard of post-operative pain management. Buprenorphine is a new semi-synthetic opioid and 0.3 mg has shown equipotent effect as 12.5 mg of morphine and 0.125 mg of fentanyl. Aims and Objectives: The aims of this study were to compare the effects of epidural and intravenous buprenorphine and clinically significant differences on perioperative hemodynamic variables, duration, and quality of analgesia and its adverse-effects. Materials and Methods: A total of 60 patients with ASA grade I/II scheduled for elective abdominal surgeries under general anesthesia were randomized into two groups. Group IA received intravenous Inj Buprenorphine 0.3 mg diluted with 10 mL of normal saline and 10 mL NS given epidurally just before the closure of peritoneum; Group EA received epidural Inj Buprenorphine 0.3 mg diluted with 10 mL of normal saline and 10 mL NS given intravenously just before the closure of peritoneum. The post-operative hemodynamic vitals, analgesia, and adverse-effects were assessed at certain intervals over 24 h. Results: In both groups, there was a significant reduction in heart rate and blood pressure as compared to baseline (pre-induction) over first 2 h–3 h following the administration. Group EA has shown to provide satisfactory, prolonged duration of analgesia 22.32 h, and better visual analog scale score as compared to Group IA 18.71 h. Conclusion: Epidural buprenorphine 0.3 mg has proved to provide higher satisfactory post-operative analgesia and considered a better alternative to 0.3 mg intravenous buprenorphine in terms of prolonged post-operative analgesia and acceptable adverse event profile.